MONITORING OF VOLUME STATUS USING A NOVEL SENSOR FOR THE ASSESSMENT OF INFERIOR VENA CAVA AREA AND COLLAPSIBILITY IN A PATIENT WITH HFREF RECEIVING ADVANCED HEART FAILURE THERAPIES - Wetterling, Friedrich (My University, 2023)
Background: A novel sensor designed to measure infe- rior vena cava (IVC) area over time was used in this study (FIRE1). The system consists of the implantable sensor and an external belt, which is worn around the patient’s ab- domen for a minute per day. The resonant frequency of the sensor is detected externally by the belt. The results provide an accurate measurement of IVC area and col- lapsibility index. Case study: A patient, 48-year-old male, had six years his- tory of chronic HFrEF due to idiopathic dilated cardiomy- opathy. The patient had stable NYHA class III symptoms at the time of enrolment in the study. The patient met the criteria for the study using this novel sensor, which was implanted in January 2020 and the system measured the changes in the patient’s IVC area over time on a daily basis. The patient was admitted to hospital because of worsening of heart failure with symptoms and signs of low cardiac output and congestion due to slow ventricular tachycardia under the ICD detection in September 2021. The patient was dependent on inotropes and referred to an advanced heart failure therapy centre. Finally, the patient received an LVAD (HeartMate 3) as a bridge to heart transplant in October 2021. The patient stayed in the study and has con- tinued to acquire daily sensor readings. The patient under- went successfull heart tranplantation on 26th March 2023. Results: We report the changes of IVC area and collaps ibility index as assessed at time of worsening of heart failure, after LVAD implantation and after heart transplantation. Conclusion: In this case study, the changes in IVC area and collapsibility index as assessed by a novel sensor system appeared to have predictive value of the subject’s deterioration towards advanced therapies, and subsequently responded positively post LVAD implantation and heart transplant.
Czech Cardiovascular Research and Innovation Days 2023